Review of Farmers Field School Approach for Facilitation of Climate Smart Agriculture - Shekmohammed, Siraj; Lemma, Samuel (Discoveries in Agriculture and Food Sciences, 2023)
Sustainable agricultural development strategies depend on ensuring farmers access technology and management techniques. Policymakers employ agricultural extension and advisory services to accomplish this goal. The extension was traditionally viewed as a 'top-down' institution, and used by policymakers to disseminate knowledge about farming to the public. These traditional extension methods have received criticism for being "one size fits all," failing to account for the wide variety of socioeconomic and institutional contexts that farmers must operate in, and failing to involve farmers in the creation of technology and practices suitable for their environments. Additionally, it was thought that more intensive strategies were required to communicate complex messages. Since the 1980s, a more inclusive methodology has been used to deliver extension services, with farmer field schools emerging as a key component. This paper examined farmer field schools as a strategy for promoting climate-smart agriculture. The paper also examined the role of this approach in promoting climate-smart agriculture and engaging the general public. A discussion of farmer field schools' experiences around the world is also included, with a focus on the effects of their methodologies. The paper also outlined the strength and weaknesses of farmer field school strategies.